PSYCHOLOGICAL CONTRACT AT WORK IN THE CONTEX OF ARMENIA AND THE UK - Barseghyan , A.E. (Modern Psychology, 2019)
Employment relationships, and in particular psychological contract, as an individuals’ perception of mutual obligations between an employer and an employee is influenced by national culture. The purpose of this research is to understand the employment relationships and psychological contracts in financial sectors of the two countries: Armenia and the UK. As a sub-objective, the researcher is seeking to identify and contrast the terms of the psychological contract, exchange relationships between employer and employee and what aspects of work are valued by knowledge workers in both countries. The interviews were conducted with 24 participants in two organisations, one from each country (Armenia and the UK). A thematic analysis revealed some cultural differences in psychological contract in two countries. The data from this study also suggests that there are similarities in psychological contract contents and work values of knowledge workers.